Réponses

Meilleure réponse !
2013-10-17T21:44:16+02:00
A= 2(3t-5)-(5t-3)(-2t+1)
  =( 6t-10)-(-10t²+5t+6t-3)
  =6t-10+10t²-5t-6t+3
   =10t²-5t-7
b = 4t-5(2t+1)+(3t-4)(7t+2)
   = 4t-10t-5+21t²+6t-28t-8
   = 21t²-28t-13
c = (3t-2)(-t+4)-(t+1)(-2t+5)
  = (-3t²+12t+2t-8)-(-2t²+5t-2t-5)
   = -3t²+12t+2t-8+2t²-5t+2t+5
   = -t²+11t-3
d = (2t-3)(t+2)-5(2t-3)
   = (2t-3)(t+2-5)
     =(2t-3)(t-3)
e = (2t-3)4t+2t-3
   = (2t-3)4t+(2t-3)
   = (2t-3)(4t+1)
2013-10-17T21:47:54+02:00
a = 2 (3t-5)-(5t-3)(-2t+1)
6t -10 -(-10t² +5t +6t -3
6t -10 +10t² -5t -6t +3
= 10t² -5t -7
b = 4t-5 (2t+1)+(3t-4)(7y+2)
4t - (10t +5) + (21t² +6t -28t -8)  je suppose que le y est une faute de frappe
4t -10t -5 +21t² +6t -28t -8
= 21t² -28t -13
c = (3t-2)(-t+4)-(t+1)(-2t+5)

-3t² +12t +2t -8 - ( -2t² +5t -2t +5)
-3t² +12t +2t -8 +2t² -5t +2t -5
= 18t² +11t -13

d = (2t-3)(t+2)-5(2t-3)
= (2t-3) (t+2) -5
= (2t-3)(t+2-5)
= (2t-3)(t -3)
e = (2t-3)4t+2t-3

= (2t-3)(4t +1)